1000 h Operational Lifetime Perovskite Solar Cells by Ambient Melting Encapsulation. Issue 9 (30th January 2020) - Ma, Sai; Bai, Yang; Wang, Hao; Zai, Huachao; Wu, Jiafeng; Li, Liang; Xiang, Sisi; Liu, Na; Liu, Lang; Zhu, Cheng; Liu, Guilin; Niu, Xiuxiu; et al.
Abstract: Improving device lifetime is one of the critical challenges for the practical use of metal halide perovskite solar cells (PSCs), wherein a reliable encapsulation is indispensable. Herein, based on an in‐depth understanding of the degradation mechanism for the PSCs, a solvent‐free and low‐temperature melting encapsulation technique, by employing low‐cost paraffin as the encapsulant that is compatible with perovskite absorbers, is demonstrated. The encapsulation strategy enables the full encapsulating operations to be undertaken under an ambient environment. It is found that the strategy not only removes residual oxygen and moisture to prevent the perovskite from phase segregation, but also suppresses the species volatilization to impede absorber decomposition, enabling a PSC devices with good thermal and moisture stability. As a result, the as‐encapsulated PSCs achieve a 1000 h operational lifetime for the encapsulated device at continuous maximum power point output under an ambient environment. This work paves the way for scalable and robust encapsulation strategy feasible to hybrid perovskite optoelectronics in an economic manner. Abstract : A novel solvent‐free and low‐temperature melting encapsulation strategy enables the full encapsulating operations under an ambient environment. It is found that the strategy not only removes residual oxygen and moisture to prevent the perovskite from phase segregation, but also suppresses the species volatilization to impede absorber decomposition, enabling a perovskite solar cell device with good thermal, moisture, and maximum power point stability.